PENGARUH KURIKULUM TINGKAT SATUAN PENDIDIKAN TERHADAP MOTIVASI BELAJAR SISWA PADA PEMBELAJARAN BAHASA ARAB KELAS VII MTS ASSSALAMIYAH GALESONG KABUPATEN TAKALAR - Ratnawati H.; Abd. Rahim Razaq; Abdul Qahar Zaenal (Al-Maraji' : Jurnal Pendidikan Bahasa Arab, 2019)
This study aims to determine the application of educational unit level curriculum in Arabic learning MTs Assalamiyah Galesong Takalar District, to determine the effect of educational unit level curriculum on Arabic learning MTs Assalamiyah Galesong Takalar District and to determine teacher efforts in arousing student motivation in learning Arabic MTs Asalamiyah Galesong, Takalar Regency. This study uses quantitative methods with a population of 204 students, where in this study a sample of 70 people from 2 classes, namely the experimental class and the control class. The data collection process used is observation, testing and documentation. From the results of the study it can be concluded that the application of the education unit level curriculum has been implemented well. Through inferential statistical tests that use the f test, obtained F table = 1.093. Then F count = 1.182 from F table = 1.093. So H0 is rejected and H1 is accepted. Thus it can be concluded that there is a very good effect of the implementation of the educational unit level curriculum on student motivation in learning Arabic class VII Mts Assalamiyah Galesong Takalar Regency.Keywords:  KTSP, Learning Motivation, Arabic Language.